Electrochemical Studies on Mixed Ligand Complexes of Cadmium Ion with Some Dicarboxylic Acids and Pyridoxine (Vitamin B6) - Sharma, Gaurav; Singh Chandel, C.P. (Asian Journal of Chemistry, 2010)
Ternary complexes of cadmium(II) with carboxylic acids (oxalic, malic, maleic, malonic and succinic acid) and pyridoxine have been studied at 300 C and at ionic strength 0.1 ( KNO3) and pH 8-9. Cadmium ion forms (0, 1),(0,2),(0,3) complexes. The reduction of the complexes in each case is reversible and diffusion-controlled. Cd(II) forms three mixed complexes, viz., [Cd (carboxylate) (pyridoxynate)], [Cd (carboxylate) (pyridoxynaten)2] and [Cd (carboxylate)2 (pyridoxynate)].